A comparative study of hand hygiene and alcohol-based hand rub use among Irish nursing and medical students. (April 2018) - Kingston, Liz M.; O'Connell, Nuala H.; Dunne, Colum P.
Abstract: Background: In Ireland, the setting for this study, the national prevalence rate of health care-associated infection (HCAI) in acute-care facilities is 5.2%. Hand hygiene and in particular hand rubbing using alcohol-based hand rub (ABHR) is highly efficacious in preventing HCAI transmission. Yet, compliance among healthcare professionals is sub-optimal. Less is known about the practices of nursing and medical students and no study comparing practices among these groups in Ireland was found. Hence, the aim of this study was to provide insight into the current hand hygiene and hand rubbing practices of nursing and medical students in Ireland and, by doing so, contribute to the broader understanding of this topic. Methods: This observational study employed a cross-sectional, self-reported design. An electronically administered questionnaire was sent to all nursing and medical students from one university. Data were analysed using appropriate software. Results: The response rate was 37% (323/872). Higher compliance with the World Health Organisation ' my five moments for hand hygiene ' model was reported among nursing students (NS) than medical students (MS), with scope for improvement in both disciplines identified. Hand hygiene compliance was highest after body fluid exposure (99.5% NS, 91% MS) and lowest after touching a patient's surroundings (61.5% NS, 57.5% MS). Attitudes towards hand rubbing were largely positive in both disciplines. 16% of NS were not aware of the clinical contraindications to ABHR use, compared to 45% of MS. 9% of NS did not know when to use soap and water and when to use ABHR, compared to 36% of MS. In contrast, more medical students (46%) than nursing students (22%) were routinely using alcohol-based hand rub for decontamination of hands as recommended. Conclusions: Results suggest scope to review current hand hygiene curricula focusing on the knowledge gaps, the practice deficits and the barriers to ABHR usage identified.